A missense mutation in a patient with developmental delay affects the activity and structure of the hexosamine biosynthetic pathway enzyme AGX1. Issue 1 (18th November 2020) - Chen, Xiping; Raimi, Olawale G.; Ferenbach, Andrew T.; van Aalten, Daan M.F.
Abstract : O ‐GlcNAcylation is a post‐translational modification catalysed by O ‐GlcNAc transferase (OGT). Missense mutations in OGT have been associated with developmental disorders, OGT‐linked congenital disorder of glycosylation (OGT‐CDG), which are characterized by intellectual disability. OGT relies on the hexosamine biosynthetic pathway (HBP) for provision of its UDP‐GlcNAc donor. We considered whether mutations in UDP‐ N ‐acetylhexosamine pyrophosphorylase (UAP1), which catalyses the final step in the HBP, would phenocopy OGT‐CDG mutations. A de novo mutation in UAP1 (NM_001324114:c.G685A:p.A229T) was reported in a patient with intellectual disability. We show that this mutation is pathogenic and decreases the stability and activity of the UAP1 isoform AGX1 in vitro . X‐ray crystallography reveals a structural shift proximal to the mutation, leading to a conformational change of the N ‐terminal domain. These data suggest that the UAP1 A229T missense mutation could be a contributory factor to the patient phenotype. Abstract :